Membangun Ekonomi Daerah di Indonesia - Frinces, Z.Heflin (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstrakOne of the Central Government of the Republic of Indonesia’s main agendas now is formulating its national economic development plan. The plan is called as Masterplan of Expediting and Expanding Indonesian Economic Development known locally as Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI). The Masterplan is designed in response to the current global economic changes and competition and by emphasizing upon regional economic development especially those regions (provinces) outside Java Island. This empahasis puts greater role of the regional government to develop their economy outonomously and independently. This article will provide some thoughts as (a) to comprehend the meaning of regional development in view of present global competition and environmental changes, (b) the significant and impact of those changes and competition upon the regional economy and (c) to suggest what the regional government should have to do in response to those environmental changes and competition in light of the Indonesian Central Government’s Masterplan. Some of the thoughts outlined here are in view of challenges faced both by the regional government and its leader currently, and suggesting some ideas of what the government and its leader have to do in creating regional’s leading competitiveness in the face of intense global competition.Keywords: regional economic development, strategic plan, strategic changes